Determination of Dam Deformation Safety Monitoring Index Based on Improved Typical Small Probability Method - ZHOU Wenzhong; GU Yanchang; HUANG Haibing; WU Yunxing (Renmin Zhujiang)
The small probability method for typical monitoring effect quantities is a common methodfor establishing early warning index based on monitoring data, but this method has someshortcomings. If the dam has not encountered the most unfavorable load or the data time series isshort, the effect quantity samples will not cover the monitoring effect quantity for the mostunfavorable load combination.This paper describes the theoretical method of determining damdeformation safety monitoring index by using the typical small probability method, proposes animproved typical small probability method by transforming the normal distribution calculation todecompose different load components with query for the standard normal distribution table, andcombined with an example of prototype observation data of a reservoir, determines the safetymonitoring index for radial displacement of section 11 of the dam. The analysis of the results ofdeformation safety monitoring index shows that the improved typical small probability method notonly is convenient for calculation but also fully considers the most unfavorable loadcombination,which increases the reliability of monitoring indexes.